Manajemen Berbasis Sekolah: Partisipasi Masyarakat dalam Implementasi Memajukan Dunia Pendidikan - Mukani Mukani (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2020)
Abstract: This article is a book review created by Ibtisam Abu-Duhou's entitled School Based Management. This is very representative book as one of the main references in understanding the school-based management (SBM) concept, since it was compiled at the very beginning when the SBM concept was introduced in Indonesia. This book consists of five chapters. The discussion begins with a review of the basic concepts, origins and character of SBM decentralization. The first chapter examines the main character of reforms and education management aspects relatively centralistic and decentralized. The second chapter discusses some research in English-speaking countries to provide answers and concrete evidence from the SBM movement. The third chapter describes the radical overall implementation of SBM in Victoria, Australia. The fourth chapter provides an example of the approach and efforts made by policy makers in identifying problems. The fifth chapter elaborates further on the material in the previous chapters to summarize the reform main characters. One consequence of implementing SBM is the realization of community participation, even as spirit and substance. Community participation is a concept of school empowerment in order to improve the quality and school independence. In implementing the SBM concept, community participation has many forms, both in educational, cultural or institutional interaction patterns.